2020
DOI: 10.20343/teachlearninqu.8.2.12
|View full text |Cite
|
Sign up to set email alerts
|

The Benefits of Academically Oriented Peer Mentoring for At-Risk Student Populations

Abstract: This article examines an academically oriented peer-mentoring program at St. John’s University. The program targeted at-risk first-year students who were having difficulty making the transition to college and matched them with trained student mentors within their major discipline. In addition to meeting with one another bi-weekly, all of the students came together for a series of organized events over the course of the academic year. The goals of the program were that mentees would (1) feel an increased sense … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
(5 reference statements)
0
7
0
Order By: Relevance
“…Research has demonstrated that participation in peer mentoring facilitates the process of meeting fellow students and forming friendships. Generally, participants in such programmes exhibit a stronger inclination towards successful social network development compared to non‐participating students (e.g., Hall et al., 2020). The second central component of social integration is contact with peer mentors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Research has demonstrated that participation in peer mentoring facilitates the process of meeting fellow students and forming friendships. Generally, participants in such programmes exhibit a stronger inclination towards successful social network development compared to non‐participating students (e.g., Hall et al., 2020). The second central component of social integration is contact with peer mentors.…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, settling into one's degree programme was facilitated by peer mentoring, with mentors providing practical information about expectations and offering advice on specific fields of study (Davis et al., 2007; Foy & Keane, 2018). Thirdly, peer mentoring positively impacted administrative work, improving students’ understanding of university jargon and encouraging them to seek out academic support services when needed (Hall et al., 2020; Lasser & Snelsire, 1996). For example, it was found that significantly more students visited their professors during office hours when they were engaged in a peer mentoring programme (Hall et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extending a student peer mentoring scheme to all students would also be highly desirable particularly during the online pivot, but, again, this requires significant staff input to run properly. A student peer mentor scheme could be tailored in such a way as to pair first year FGS with their more experienced peers, offering an important extra plank of academic and social support (Hall et al, 2020;Venegas-Muggli et al, 2021). SGIA established such a scheme for the academic year 2020-21 and is hoping to assess its impact.…”
Section: Social Factorsmentioning
confidence: 99%
“…In both structured and informal mentoring initiatives for college students, the functions of these evolving mentoring relationships may loosely follow three stages: mentoring into college life, mentoring through development of advanced skills and knowledge, and mentoring onward to life after college (McKinsey 2016). Students, staff, and faculty (i.e., academic staff) all can serve as mentors, although they may support different functions; for example, near-peers (e.g., a college senior in relation to a first-year student or a recent alumnus in relation to a college junior) often provide effective mentoring in, contributing to students' sense of belonging as they transition into college life and improving retention (Crisp et al 2017;Hall, Serafin, and Lundgren 2020).…”
Section: Introductionmentioning
confidence: 99%